X2+12x-261=0

Simple and best practice solution for X2+12x-261=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X2+12x-261=0 equation:



X2+12X-261=0
We add all the numbers together, and all the variables
X^2+12X-261=0
a = 1; b = 12; c = -261;
Δ = b2-4ac
Δ = 122-4·1·(-261)
Δ = 1188
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1188}=\sqrt{36*33}=\sqrt{36}*\sqrt{33}=6\sqrt{33}$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-6\sqrt{33}}{2*1}=\frac{-12-6\sqrt{33}}{2} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+6\sqrt{33}}{2*1}=\frac{-12+6\sqrt{33}}{2} $

See similar equations:

| 5w-5=-5(w+9) | | -c=-100 | | t÷9=1-12 | | 2x-42=-8x+28 | | 44=11n+11 | | Y=-12x+1 | | 5h+12≤=-5 | | 4(13)=b | | 2u+3(u+4)=7 | | 2x=27=-5 | | (12x-4)-(17x+8)=42 | | (4x+1-)-(=3x+5) | | 8x+4x=47 | | -14z=9-13z | | 3x^2+4=-80 | | |5x-25|+45=45 | | 3q-(2q-3)=-8 | | 6k-6=9k+15 | | −108=2x+3(4x−8) | | 15+16+d=55 | | -(x+2)+5(3x-5)=-5 | | -20+3n+1=-10n+20 | | 2k+15+70k=180 | | 3.5x+12=2.5x+16 | | 13-2x=x-5 | | 150m-100m+39,000=40,600-150m | | 11r-4=10r-4+r | | 2.5(2x-5)=7.5 | | 120+2x=10x | | 0.5b+10=0.3b+6.2 | | 14=8(q+7)-q | | 9m=-7+8m |

Equations solver categories